Case report: Microwave ablation is a safe and effective method for primary hyperparathyroidism in pregnancy - Luo, Yunbo; Lv, Qi; Xu, Zhou; Fang, Jiang; Pu, Hongyu; Gao, Yanchun; Qian, Shuangqiang; Chen, Fei; Zhao, Xiaobo; Hou, Lingmi (Frontiers in Medicine, 2024)
Primary hyperparathyroidism (PHPT) is a rare disease in pregnancy and endangers the health of both pregnant women and fetuses. However, the treatments are very limited for PHPT and most of them are unsatisfactory because of the peculiar state in pregnancy. The only curable method is parathyroidectomy which can be safely performed in the second trimester of pregnancy. In this case, we reported a pregnant woman with primary parathyroid adenoma presenting hypercalcemia and severe vomit at the end of first trimester. Finally, she got cured by microwave ablation at the end of first trimester and gave birth to a healthy baby boy.